DESIGN PROCESSES OF CONTROLLING IN DISSEMINATION OF INFORMATION IN IP-BASED NETWORKS - Казимир, В.В.; Кенійз, Я.Я.; Черних, Д.О. (Science-based technologies, 2009)
In this article described a way of the design of processes Сarboy distribution  information  in  ІР-net, which is based on the use utilizing of mathematical vehicle Petrinets, namely Е-net. Thanks to that, which is actually  in fact modeling by management algorithm, models which are in researching  explore can be used directly  imme-diatel during realization the control of system by a process Сarboy distribution of information. Not only is the generation of vocal message communication and procedure proc of routing but also methods of defences dis-played in models, that used. Realization and research work-up of models takes a place by means of the specially developed system of imitation  look-alike modeling  imagineerimg. The variant analysis of processes Сarboy of management passing the information processes  Сarboy  is offered in cellular  honeycomb  communication  net-works by means of  the system of imitation  look-alike design  imagineerimg of JESS and management signals in network by the analysis of output information of the system by the use  utilizing of feed-back by the use of new firsttime modification of formal vehicle of Е-net — Control Evaluation Net. Which becomes stands a necessary in our case, when vocal information transformation into the speed velocity flow of data information and passing on a communication channel, a few a little times changes the form shape, which results in  to unforeseeable re-sults and possible deformation disfigurement of information, the problem of realization of all information trans-formations in real-time, namely in the rate tempo of vocal talk.